Chronic application of alcohol-soluble gluten extract over undamaged skin causes clinical sensitization for life-threatening anaphylaxis via activation of systemic Th2 immune responses in mice - Jorgensen, Rick; Gao, Haoran; Chandra, Shivam; Sundar, Vaisheswini; Loy, Jaden; Van Antwerp, Chris; Ng, Perry K. W.; Gangur, Venu (Frontiers in Allergy, 2023)
Gluten allergy is a major public health problem that is growing at an alarming rate. Specific mechanisms underlying sensitization to gluten remain incompletely understood. Currently, it is unclear whether chronic exposure to alcohol-soluble gluten extract via undamaged skin has the capacity to clinically sensitize mice for life-threatening anaphylaxis. Using an adjuvant-free mouse model, here we tested the hypothesis that chronic application of alcohol-soluble durum gluten (ASDG) extract will clinically sensitize mice for life-threatening anaphylaxis. This study was2 conducted in a gluten-free Balb/c mouse colony that was established and maintained on a plant protein-free diet. Groups of adult female mice were exposed dermally to ASDG extract or vehicle once a week for 9-weeks. Specific (s) and total (t) IgE levels were quantified. Mice were challenged systemically with ASDG to measure symptoms of systemic anaphylaxis. Hypothermic shock response (HSR) and mucosal mast cell degranulation response (MMCR) were determined upon challenge. Spleen Th1, Th2, and other immune markers were quantified. We found that chronic exposure to ASDG elicited robust elevation of sIgE and tIgE. Systemic challenge with ASDG, but not vehicle, elicited life-threatening anaphylaxis associated with dramatic HSR and MMCR.Correlation analysis demonstrated direct positive inter-relationships among IgE, HSR, and MMCR.Anaphylaxis was associated with significant elevation of prototypic Th2 but not Th1 immune markers in the spleen. Our study collectively demonstrates that ASDG is intrinsically allergenic; and chronic exposure to ASDG via undamaged skin can clinically sensitize mice for life-threatening anaphylaxis via activating the systemic Th2 immune responses.